Analisis Faktor Penyebab Kesulitan Belajar IPAS Siswa Kelas IV SDN 40 Cakranegara - Fani Sulastri; Mohammad Liwa Ilhamdi; Hikmah Ramdhani Putri (Lembaga Bale Literasi, 2025)
Learning difficulties are conditions where students experience difficulties in understanding subject matter, so that the learning outcomes obtained do not match their abilities. This study aims to determine the factors causing learning difficulties in Natural and Social Sciences (IPAS) for fourth-grade students at SDN 40 Cakranegara. Data collection methods were carried out using questionnaires and interviews. The data analysis technique used was Miles and Huberman with analysis components including data reduction, data presentation, and conclusion drawing. The results showed that learning difficulties in IPAS are influenced by internal and external factors. Based on the questionnaire results, the contribution of internal factors includes learning attitude (15.70%), motivation (23.24%), and interest (21.66%), while external factors consist of family (22.74%) and school (17.03%). In detail, from internal factors, students' learning attitudes are still low, especially in the indicators of self-confidence and feelings; learning interest is low in the indicators of attraction and feeling of pleasure; and motivation is not yet optimal in the indicators of initiative and commitment. From external factors, the school's social environment is not fully supportive because students lack encouragement from peers, while from the family side, an unsupportive home atmosphere, unsupportive parenting styles, and economic limitations were found. The learning difficulties in IPAS among fourth-grade students are the result of the interaction between weak internal factors and lack of external support, thus requiring synergy between teachers, schools, and parents to help students overcome learning difficulties more optimally.